Analisis Komparatif Konsep Spiritualitas dalam Ajaran Agama Islam, Hindu dan Buddha - Muh Rizaldi (STAI Al-Mujtama Pamekasan, 2022)
Abstract: This article examines the concept of human spirituality as a spiritual being (homo religious) from the perspective of Islam, Hinduism, and Buddhism. The aim is to find common ground related to human spirituality in the teachings of Islam, Hinduism, and Buddhism based on information from the scriptures of each religion. This research uses a comparative study method with exoteric and esoteric paradigms. The results of this study indicate that, in the exoteric realm between Islam, Hinduism, and Buddhism about human spirituality, there are different methods. Still, the differences are not contradictory but only systematic. The esoteric realm is generally oriented to the same dimension: the achievement of transcendental union or union with God. Keywords: Spirituality, Human, Religion, Exoteric, Esoteric